Molecular Docking and Antimicrobial Evaluation of Some Novel Pyrano[2,3-C] Pyrazole Derivatives - Leila Emami; Leila Zamani; Razieh Sabet; Kamiar Zomorodian; Zahra Rezaei; Zeinab Faghih; Yeganeh Shahbazi; Soghra Khabnadideh (Shiraz University of Medical Sciences, 2020)
The extensive use of antifungal drugs and their resistance against fungal infections have led to develop novel antimicrobial compounds. In this research, 14 new pyranopyrazole compounds (D1-D14) which were synthesized before, screened for antimicrobial activity. These compounds consist of a pyranopyrazole scaffold with a phenyl substitution at the 4-position of the pyran ring. Antimicrobial evaluation of the above compounds were investigated against different species of fungi, gram positive and gram negative bacteria by broth micro dilution methods as recommended by CLSI. The specific binding mode or the binding orientation of the compounds to CYP51 active site, have been also performed by molecular modeling investigations. Our results implies that some of our compounds possess desirable inhibitory activity against the tested microorganisms. Our docking study results also showed that the binding free energy values of the compounds are in agreement with the corresponding experimental activity values. By comparison the relationship between chemical structures and biological activities revealed that the presence of a withdrawing substituent at4-position of phenyl group at para position of the pyran ring enhance the antimicrobial activity.